2021
DOI: 10.3389/fspor.2020.546205
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Macro-Kinematic Strategies During the Rounds of a Cross-Country Skiing Sprint Competition in Classic Technique

Abstract: This study was designed to examine macro-kinematic parameters of six female cross-country skiers during the qualifying, semi-final and final rounds of a 1.1 km sprint competition in classical technique. During each round these skiers were monitored continuously with a single micro-sensor, and their cycle parameters and relative use of these two sub-techniques calculated. Within each round six sections of the course, during which all skiers employed either double pole (DP) or diagonal stride (DS) sub-technique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Although better-performing skiers produced longer CL and higher CR in DIA in the last uphill segment, all skiers selected similar sub-techniques during the race as seen with both the individual use of sub-techniques and the percentage use of sub-techniques in relation to distance (Figs 4 and 5). These findings are, however, in contrast to those of Marsland et al [30] who found larger variations in sub-technique selection during a classical sprint race. A plausible explanation for this might be the differences in topography and race strategy between the two studies.…”
Section: Plos Onecontrasting
confidence: 99%
See 4 more Smart Citations
“…Although better-performing skiers produced longer CL and higher CR in DIA in the last uphill segment, all skiers selected similar sub-techniques during the race as seen with both the individual use of sub-techniques and the percentage use of sub-techniques in relation to distance (Figs 4 and 5). These findings are, however, in contrast to those of Marsland et al [30] who found larger variations in sub-technique selection during a classical sprint race. A plausible explanation for this might be the differences in topography and race strategy between the two studies.…”
Section: Plos Onecontrasting
confidence: 99%
“…A plausible explanation for this might be the differences in topography and race strategy between the two studies. In addition, the fact that the skiers in the previous study by Marsland et al [30] were women while our study sample included men only may to some degree explain this difference in sub-technique selection as shown previously in a classical distance race [44]. Furthermore, the skiers in the heats in sprint XC skiing are often grouped during the race, and the skiers in our study mainly used the same sub-technique as the skiers in front.…”
Section: Plos Onementioning
confidence: 85%
See 3 more Smart Citations